PERAN INSPEKTORAT KABUPATEN TIMOR TENGAH SELATAN DALAM MELAKUKAN PENGAWASAN PENGELOLAAN KEUANGAN DANA DESA PADA KECAMATAN KOTA SOE - Taneo, Ovi Yuvita; Pau, Sarlin P. Nawa; Muga, Maria Prudensiana Leda (Universitas Nusa Cendana, 2023)
This research aims to determine the role of the South Central Timor Regency Inspectorate in supervising financial management of village funds in Soe Citysub-district. The data used in this research was obtained using interviews and field observation methods. This research uses a qualitative research approach. The informants in this research were the auditor at the Inspectorate of South Central Timor Regency, the village head and the staff in Kuatae village and Noemeto Village, Soe City sub-district. This research focuses on the role of the inspectorate with research points including the role of regional inspectorates, supervision and village funds. The analytical method used is the method developed bye Miles and Huberman (1984) with the Nvivo Software tool. The result of this research state that the role of the regional inspectorate in supervising village funds in Kota Soe sub-district is more focused on training to minimize the occurence of misappropriation of village funds.